Undertaking a Participatory Rangeland Resource Assessment in Arbahajan Ward, Wajir County, Kenya - The International Livestock Research Institute (ILTI) (Accelerating Impacts of CGIAR Climate Research for Africa, 2024)
Participatory rangeland management is a step-by-step process to build capacity of rangeland communities to better manage their land and resource in the face of new challenges. This film describes how to do a PRM participatory rangeland resource assessment - the first step in the Implementation stage before rangeland management planning takes place.